Cenozoic Sediment Provenance in the Northern Great Plains Corresponds to Four Episodes of Tectonic and Magmatic Events in the Central North American Cordillera. Issue 10 (29th October 2018) - Li, Lin; Fan, Majie
Abstract: Detrital zircon U‐Pb provenance in the northern Great Plains reveals histories of drainage reorganization of the paleo‐Missouri River in response to Cenozoic tectonic and magmatic processes in the central North American Cordillera. During the latest Cretaceous, sediment provenance was confined to the Cordilleran hinterland in central Idaho and southwestern Montana, probably due to the existence of a subtle paleohydraulic divide in northwestern Montana. During the early to middle Paleocene, the paleodrainage was expanded to cover the Belt Supergroup in northwestern Montana in response to the eastward propagation of the Cordilleran thrust belt. During the late Paleocene to early Eocene, the final movement of the thrust belt and the initial extension of the Cordilleran hinterland shifted the drainage divide to the orogenic front and caused focused erosion of the upper Lower to Upper Cretaceous rocks to the east. During the middle Eocene to early Oligocene, a significant increase of Archean grains suggests renewed exhumation of the Laramide province and sediment delivery by the paleo‐Yellowstone River originated in the central Rocky Mountains. The presence of middle Eocene to early Oligocene zircons during this stage also suggests headwater erosion of the paleo‐Upper Missouri River into the Dillion volcanic field in southwestern Montana. These interpretations indicate that a drainage pattern similar to that of the modern Missouri River was established during middle Eocene to early Oligocene time. The detrital zircon maximum depositional ages also improve the chronostratigraphic framework of the Paleogene strata. Our study demonstrates that orogenic processes can be well archived in sedimentary records far away from orogenic systems. Key Points: Changes in detrital zircon U‐Pb signature reflect four tectonic and magmatic events in the central North American Cordillera Drainage of the paleo‐Missouri River was likely established during middle Eocene to early Oligocene renewed Laramide exhumation Sediment provenance records far away from orogenic systems can archive orogenic processes